The Atmosphere of inter-Company Cooperation - Czakon, Wojciech (Studia Oeconomica Posnaniensia, 2017)
The organizational climate construct has greatly contributed to our under-standing of human behaviour and the resulting performance of organizations. It has the merit to link a microfoundation, i.e. individual perceptions of a work environment, with aggregate phenomena such as productivity or innovativeness. In strategic management perceptions of the environment is also grounded as a moderating variable for decisions, behaviours and performance. Directly transposing an organizational climate to inter-organizational phenomena is not possible. A conceptualization of an inter-organizational collaboration climate is proposed and based on the concurrent analysis of inter-organizational climate in strategic management research at dyad and network levels, and of inter-organizational environments distinctive features. A definition and three dimensions are proposed.